Mobile Web-Based Cassava Inventory Management System: A Case Study at CV Panca Yoga, Purbalingga - Pratama, Haris Andika; Wulandari, Sri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
A web and mobile-based inventory management system is developed with the aim of streamlining the process of checking incoming goods, outgoing goods, stock inventory, and report generation for business owners and employees. CV Panca Yoga, operating in the cassava trading industry since 2012 and located on Jalan Raya Kejobong, Krenceng, Purbalingga, Central Java, serves as a case study. The existing inventory data recording processes at CV Panca Yoga are considered inefficient and ineffective, as they rely on manual procedures for recording incoming and outgoing goods, managing stock inventory, and generating reports. To address these issues, we have designed a web and mobile-based inventory management application that facilitates the input of data related to incoming and outgoing goods, stock inventory, and report generation. This digitized system not only enhances speed and efficiency but also reduces the potential for errors.